Tsc1 represses parvalbumin expression and fast-spiking properties in somatostatin lineage cortical interneurons - Ruchi Malik (Nature Portfolio, 2019)
Although cortical GABAergic interneuron (CIN) dysfunction is implicated in several neuropsychiatric disorders, we still know very little about how they attain their unique properties or how their dysfunction impacts neuropsychiatric disorders. In this study, authors show that conditional loss of Tsc1, causes SST+ CINs, which are distinct from PV+ CINs, to express PV and adopt fast-spiking properties, via MTOR activity